Scientists must write : - Barrass, Robert. (Routledge, 2002)
This book, by a scientist, will help reader to write: to observe, remember, think and plan; to manage your time and avoid stress; and to improve your communication skills. Extensively revised and updated, this valuable reference takes into account the huge changes in information technology since the very successful first edition